Gold nanowire electrodes for flexible organic thin-film transistors. (1st September 2022) - Takane, Satoshi; Noda, Yuki; Toyoshima, Naomi; Uemura, Takafumi; Bando, Yuki; Sekitani, Tsuyoshi
Abstract: A flexible organic thin-film transistor (OTFT) with gold nanowire (AuNW) networks as source/drain/gate electrodes (AuNW-OTFT) was fabricated and characterized. Its fabrication was enabled by the successful formation of AuNW network electrodes on a flexible thin-film substrate using the thermal pressing transfer method. The fabricated AuNW-OTFT exhibited typical p-type characteristics (mobility: 6.0 × 10 −2 cm 2 V −1 s −1, on/off ratio: 10 5 ) and a lower contact resistance than that of an OTFT with vacuum-deposited Au electrodes in the same configuration. Furthermore, the AuNW-OTFT demonstrated high mechanical durability, as proven by the absence of significant characteristic changes before and after bending (bending radius:0.8 mm).